2004
DOI: 10.1111/j.1365-3156.2004.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a double dose of sulphadoxine–pyrimethamine to reduce prevalence of pregnancy malaria in southern Mozambique

Abstract: SummaryMalarial infection during pregnancy increases the risks of severe sequelae for the pregnant woman and the risk of delivering a low birthweight baby. The aim of this intervention study was to reduce significantly the prevalence of malaria parasitaemia in adolescent parturients in Matola and Boane in Mozambique. The study was focused upon the most malaria-vulnerable group, adolescent nulliparous and primiparous women. After completing the usual antenatal clinic and giving informed consent, 600 pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 41 publications
(36 reference statements)
6
47
0
Order By: Relevance
“…Trials were not included if they compared multiple drugs with no inactive control [53][54][55] or could not be matched to entomologic data. 56 The estimates refer to primigravidae, or primigravidae and secundigavidae together in the case of one trial. ࡗ ‫ס‬ chloroquine; ‫ס‬ dapsone-pyrimethamine; ᭡ ‫ס‬ sulfadoxinepyrimethamine; ᭹ ‫ס‬ pyrimethamine.…”
Section: Discussionmentioning
confidence: 99%
“…Trials were not included if they compared multiple drugs with no inactive control [53][54][55] or could not be matched to entomologic data. 56 The estimates refer to primigravidae, or primigravidae and secundigavidae together in the case of one trial. ࡗ ‫ס‬ chloroquine; ‫ס‬ dapsone-pyrimethamine; ᭡ ‫ס‬ sulfadoxinepyrimethamine; ᭹ ‫ס‬ pyrimethamine.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of peripheral malaria parasitaemia at 34 weeks gestation of 6.3% among the participants in the SP group, is lower than 8.7% from southern Mozambique, 11.9% from Benin city and 10.4% from Ibadan in Nigeria, which may probably be because only primigravida were used in this study, while in these studies from southern Mozambique, Benin City and Ibadan, multigravid women were also involved [15,22,25,26]. This may be explained by the findings of Gies et al from Burkina Faso, that SP is more effective in preventing malaria parasitaemia among primigravida than among women of higher parity [27].…”
Section: Discussionmentioning
confidence: 61%
“…This showed that the effectiveness of SP-IPTp in preventing malaria in pregnancy is similar to that of proguanil, which shows that SP-IPTp is still effective in the prevention of malaria in pregnancy at Aminu Kano Teaching Hospital, despite reported cases of resistance in southern Asia and some part of Africa [15][16][17][18][19]. The similar mean packed cell volume between the two groups at recruitment showed that the base line PCV at recruitment did not contribute any bias in the final PCV at 34 weeks gestation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Pyrimethamine is a dihydrofolate reductase inhibitor and slow-acting blood schizonticide for all malaria strains and is usually given in combination with sulphadoxine. Unlike other folic acid antagonist, pyrimethamine has no teratogenic effect and can be used for treatment and prophylaxis (2,3,25). Although these drugs are generally considered safe for treating malaria in pregnancies, drug interactions with human placenta still needs to be addressed.…”
mentioning
confidence: 99%